2016
DOI: 10.1111/jspn.12157
|View full text |Cite
|
Sign up to set email alerts
|

Does the visibility of a congenital anomaly affect maternal–infant attachment levels?

Abstract: It is important to apply appropriate nursing interventions for these mothers during the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
(87 reference statements)
0
13
0
3
Order By: Relevance
“…Unplanned pregnancy, father's negative reaction to the pregnancy, long duration of labour, method of delivery, absence of early contact with the newborn, infant feeding method, and maternity blues have been identified as impacting early maternal attachment (Cetisli et al, ; Nagata et al, ; Pascoe & French, ; Troy, ). During the months after birth, pre and post‐partum depressive symptoms, low level of partner satisfaction, low social support, separation with the baby during the first days, prenatal attitudes and expectations, and a history of childhood sexual abuse increase the risk of low maternal attachment to the child (Boztepe, Ay, Kerimoglu Yildiz, & Cinar, ; Mutlu, Erkut, Yıldırım, & Gündoğdu, ; Nieto, Lara, & Navarrete, ; Peterson & Mehl, ). In addition, having an infant who suffers from excessive crying has been associated with lower levels of maternal attachment (Bond, Prager, Tiggemann, & Tao, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unplanned pregnancy, father's negative reaction to the pregnancy, long duration of labour, method of delivery, absence of early contact with the newborn, infant feeding method, and maternity blues have been identified as impacting early maternal attachment (Cetisli et al, ; Nagata et al, ; Pascoe & French, ; Troy, ). During the months after birth, pre and post‐partum depressive symptoms, low level of partner satisfaction, low social support, separation with the baby during the first days, prenatal attitudes and expectations, and a history of childhood sexual abuse increase the risk of low maternal attachment to the child (Boztepe, Ay, Kerimoglu Yildiz, & Cinar, ; Mutlu, Erkut, Yıldırım, & Gündoğdu, ; Nieto, Lara, & Navarrete, ; Peterson & Mehl, ). In addition, having an infant who suffers from excessive crying has been associated with lower levels of maternal attachment (Bond, Prager, Tiggemann, & Tao, ).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal depression, which has been acknowledged as a predictor for bonding disorders [22,23], statistically impacts the association of maternal bonding disorders with CL/P birth, because mothers with CL/P birth are generally troubled with more parenting and/or caregiving issues with regard to feeding and breathing developments [5][6][7]. Furthermore, because the visual impacts of cleft lip possibly influence the processing of maternalto-infant bonding as suggested by Boztepe et al [12], we focused on whether the prevalence of cleft lip was associated with bonding disorders among advanced-age multiparae. Consequently, the significant association of bonding disorders with prevalence of CL±P birth did not remain after the adjustment using all covariates (OR [95% CI] = 2.31 [0.93-5.73], p = 0.072).…”
Section: Discussionmentioning
confidence: 99%
“…Most of this maltreatment was in the form of supervisory neglect (about 70%); however, a significantly higher risk of medical neglect was also observed [10,11]. Boztepe et al also indicated that, in comparison with congenital heart disease, cleft lip was more likely to adversely affect maternal emotional connection toward the infant possibly due to the visual aspects of the condition [12]. Indeed, there is increasing evidence suggesting potential impairments of infant-maternal attachments among children with CL/P [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Diğer taraftan, yapılan çalışmalarda olduğu gibi bu olguda da konjenital anomalinin çoklu majör ve görsel anomali olup, uzun süreli sonuçları olması uyumu ve bağlanmayı azaltabilecek bir faktör olarak değerlendirilmiştir. 10,17 Ayrıca, uzun süre hastanede yatışlar (16 hafta) anne ile bebeğin birlikte geçirdikleri süreyi oldukça kısıtlamıştır ve bu durum bağlanma sürecini güçleştirmiştir. Annenin hastanede kuvöz içinde olan bebeğinin yanında kalabildiği sürelerde, bakımlar sırasında, annenin bakım davranışları ve ruhsal durumu izlenmiştir.…”
Section: Discussionunclassified
“…[1][2][3] Konjenital anomalili ve sağlıklı bebeği doğan annelerin, anne-bebek bağlanmasının değerlendirildiği deneysel bir çalışmada, konjenital anomalili bebeği olan annelerin bağlanma dü-zeyinin sağlıklı bebeği olan annelere göre daha düşük ve aralarındaki farkın istatistiksel olarak anlamlı olduğu bulunmuştur. 10 Annelik rolünün uygulanmasına paralel olarak, doğumdan sonra başlayan bebekteki bağlanma davranışları ise meme arama, başı döndürme, emme, yutma, parmak emme, yakalama, anneye yönelme, beslenme saatlerini sezinleme ve emmeye hazırlanma şeklinde kendisini göstermektedir. 11 Koanal atrezi nedeni ile uzun süre hastanede annesi yanında olmaksızın yatan bir bebeğin gelişiminin incelendiği bir çalış-mada; başlangıçta yalnızca ışıklı uyaranlara yanıt veren, göz teması kurmayan ve dış uyaranların farkında olmayan bebeğin, annesinin yanında kalması ve evde bakımını devam ettirmesi sonucunda, taburcu olduktan bir ay sonra ki gelişim ölçeğinden yüksek puan aldığı görülmüştür.…”
Section: Bebeği Konjenital Anomalili Doğan Anneninunclassified